Urinary concentrations of bisphenol A, parabens and phthalate metabolite mixtures in relation to reproductive success among women undergoing in vitro fertilization. - Mínguez-Alarcόn, Lidia (Environ Int, 2019)
BACKGROUND: We have previously investigated whether urinary concentrations of bisphenol A (BPA), parabens, and phthalate metabolites were individually associated with reproductive outcomes among women undergoing in vitro fertilization (IVF) treatment. However, humans are typically exposed to many man-made chemicals simultaneously. Thus, investigating one chemical at a time may not represent the effect of mixtures. OBJECTIVE: To investigate whether urinary concentrations of BPA, parabens, and phthalate metabolite mixtures are associated with reproductive outcomes among women undergoing IVF. METHODS: This prospective cohort study included 420 women contributing 648 IVF cycles who provided up to two urine samples per cycle prior to oocyte retrieval (N=1,145) between 2006 and 2017 at the Massachusetts General Hospital Fertility Center, and had available urine biomarker data. Urinary concentrations of BPA, parabens, and phthalate metabolites were quantified using isotope-dilution tandem mass spectrometry. Intermediate and clinical end-points of IVF treatments were abstracted from electronic medical records. Principal component analysis (PCA) and bayesian kernel machine regression (BKMR) were used to identify main patterns of BPA, parabens, and phthalate metabolites concentrations. We used generalized linear mixed models to evaluate the association between PCA-derived factor scores, in quartiles, and IVF outcomes, using random intercepts to account for multiple IVF cycles and adjusting for known confounders. Because of temporal trends in exposure, we conducted a sensitivity analysis restricted to women who underwent IVF cycles in the earlier years of study (2006–2012). RESULTS: Urinary concentrations of BPA, parabens, and most phthalate metabolites were significantly lower during the second half of the study period (2013–2017) than during the first half (2006–2012). None of the three factors derived from the PCA [di(2-ethylhexyl) phthalate (DEHP), non-DEHP, and paraben] was associated with IVF outcomes in the main analyses. Similarly, BKRM analyses did not identify any associations of individual urinary concentrations of BPA, paraben and phthalate metabolites with IVF outcomes while accounting for correlation between exposures. However, in sensitivity analyses restricted to women who underwent IVF cycles from 2006 to 2012, where concentrations of most phthalates and phenols were highest, there were decreases in implantation, clinical pregnancy, and live birth across quartiles of the DEHP factor. Specifically, women in the highest quartile of the DEHP factor had, on average, lower probabilities of implantation (−22% p, trend=0.08), clinical pregnancy (−24% p, trend=0.14), and live birth (−38% p, trend=0.06) compared to women in the lowest quartile. Among this group of women, BKMR results did not identify any single contributor driving the decreased probabilities of live birth within the DEHP factor. CONCLUSIONS: We confirmed that women undergoing IVF are concurrently exposed to multiple endocrine disrupting chemicals (EDCs). While we found no overall significant associations, we observed diminished pregnancy success with specific clusters of chemicals among women who underwent IVF cycles in earlier years of study, when urinary concentrations of these EDCs were higher.